KEBIJAKAN PERIJINAN DAN UPAYA PENINGKATAN PELAYANAN MELALUI ADMINISTRATIEF BEROEP - Tri Widodo W. Utomo (Pusjar SKPP Lembaga Administrasi Negara, 2005)
The enactment of new decentralization framework has been unwisely implemented in many regions. Districts/city governments tend to promulgate new local taxes and levies result in high cost economy for regional business activities. The principle of delivering administrative approval (perijinan) is also misgiving as it is deployed for all people’s economic facets. Philosophically, not everysingle economic activity requires such kind of permission. This situation leads to the deprivation of public service quality. In order to restore government performance in delivering public services, this paper tries to offer a solution from the perspective of constitutional / public administration law (hukum administrasi negara), i.e. providing new mechanism of administratief beroep or administrative legal efforts (upaya hukum secara administratif).